The Impact of Foreign Direct Investment on the Nigeria Manufacturing Sector: A Time Series Analysis - Rasaq Akonji Danmola; Adijat Olubukola Olateju; Abubakar Wambai Aminu (European Scientific Journal, ESJ, 2017)
The objective of the study reveals that FDI in the Manufacturing sector exacts a positive influence on the manufacturing output and the impact is statistically significant. This result further confirms the effectiveness of economic policy of the federal government of Nigeria through the adoption of liberalized industrial and trade policies. These policies were undertaken with a view to improve efficiency and productivity, as well as to improve the competitiveness of the Nigerian manufacturing industry. The policy implication is that,in order to maintain sustainable economic growth and development, a positive domestic investment is a prerequisite for increasing the flow of foreign investment in the manufacturing sector. Nigeria, while continuing to encourage inward FDI, efforts should be made to channel it into the manufacturing sector so as to accelerate the diversification process. In addition, the implementation of policy of trade liberalization should be reviewed and implemented with caution. The policy that will further make the economy more-import dependent will not augur well for the economy.